Modelling ripple morphodynamics driven by colloidal deposition. (15th February 2018) - Hewett, James N.; Sellier, Mathieu
Highlights: We modelled colloidal silica particle deposition driven by Brownian diffusion. A near-wall subdomain was employed for reducing the computational expense of runs. Micron sized surface roughness enhanced the particle deposition rate. Ripples of silica deposit, which were perpendicular to the flow, migrated upstream. The node shuffle algorithm improved the mesh evolution of the fluid-silica interface. Abstract: Fluid dynamics between a particle–laden flow and an evolving boundary are found in various contexts. We numerically simulated the morphodynamics of silica particle deposition from flowing water within geothermal heat exchangers using the arbitrary Lagrangian–Eulerian method. The silica particles were of colloidal size, with submicron diameters, which were primarily transported through the water via Brownian motion. First, we validated the Euler–Euler approach for modelling the transport and deposition of these colloidal particles within a fluid by comparing our simulation results with existing experiments of colloidal polystyrene deposition. Then we combined this multiphase model with a dynamic mesh model to track the gradually accumulated silica along the pipe walls of a heat exchanger. Surface roughness was modelled by prescribing sinusoidally–shaped protrusions on the wall boundary. The silica bed height grew quickest at the peaks of the ripples and the spacing between the protrusions remained relatively constant. The rough surface experienced a 20% reduction in silica deposition when compared to a smooth surface. We also discuss the challenges of mesh deforming simulations with an emphasis on the mesh quality as the geometry changes over time.